2018
DOI: 10.15809/irriga.2016v21n3p561-576
|View full text |Cite
|
Sign up to set email alerts
|

Déficit Hídrico Nas Fases Vegetativa E De Floração Da Pimenta ‘Tabasco’ Em Ambiente Protegido

Abstract: DÉFICIT HÍDRICO NAS FASES VEGETATIVA E DE FLORAÇÃO DA PIMENTA ‘TABASCO’ EM AMBIENTE PROTEGIDOLÍGIA BORGES MARINHO 1; JOSÉ ANTONIO FRIZZONE2; JOÃO BATISTA TOLENTINO JUNIOR3; JANAÍNA PAULINO4; JOSÉ MONTEIRO SOARES5 E FRANCISCO NOGUEIRA VILAÇA6*Artigo extraído da tese do primeiro autor1 Enga. Agrônoma, Doutora, Profa. Departamento Tecnologia e Ciências Sociais, Universidade do Estado da Bahia, av. Edgard Chastinet, São Geraldo, CEP 48905-680, Juazeiro, BA. Fone (74) 3611-7363. E-mail: ligia.bmarinho@gmail.com2 En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…These results corroborate with Marinho et al (2018), with the authors considering that the pepper plants have three growth phases: vegetative, flowering-fruiting and fruit maturation. The authors consider that the duration of the growth stages of pepper crop depends on the species, the type of cultivar as well as the edaphoclimatic conditions.…”
Section: /7supporting
confidence: 92%
See 1 more Smart Citation
“…These results corroborate with Marinho et al (2018), with the authors considering that the pepper plants have three growth phases: vegetative, flowering-fruiting and fruit maturation. The authors consider that the duration of the growth stages of pepper crop depends on the species, the type of cultivar as well as the edaphoclimatic conditions.…”
Section: /7supporting
confidence: 92%
“…This crop cultivars have three growth stages: vegetative, reproductive (flowering and fruiting) and fruit maturation. (Marinho et al, 2018). They have two growth types, determined and undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…The production of the mixture of commercial substrate + carbonized rice husk demonstrates that despite the treatment had suffered from foliar abscission at the beginning of crop fructification likely due to water stress, S2 managed to obtained higher results for the yield and water use efficiency components. Marinho et al (2016) observed that water deficit in tabasco pepper at different development phases provided smaller productivity to the plant at the vegetative stage compared to the water deficit at the reproductive phase. However, the irrigation depth that provided the most significant production at both times was 100% of the evapotranspiration of the crop, thus corroborating with this study.…”
Section: Resultsmentioning
confidence: 96%
“…Although the highest fruit production having been observed for an irrigation depth of 101.47% WHC, the best relationship between production and water applied was obtained for an irrigation depth of 69.17% WHC. Just as for production, the treatment with substrate S2 presented the best result for water use efficiency, with an and Marinho et al (2016) when assessing water use efficiency for the tabasco pepper (Capsicum frutescens), they observed that the irrigation depth of 40% crop evapotranspiration, presented the best result for WUE. In contrast, when evaluating WUE in a sweet pepper crop (Capsicum annuum L.), Ćosić et al (2015) observed that the treatment that received irrigation depth of 100% crop evapotranspiration presented the highest WUE, as well as higher production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation